La universidad pública bajo ataque neoliberal - Corrales Arias, Adriano (2020)
The following article seeks to encourage the discussion about threats against the public university as well as its necessary defense. A historical account is made of the origins of the western university and the future of the Costa Rican public university. The attacks and threats coming from the neoliberal counter-reform since the eighties of the last century stand out. These attacks and threats are reinforced by the presence of sectors within the universities that support and underpin the “reforms” proposed by the counter-reform. These attitudes and actions, plus the attacks, overlap with partial struggles in defense, certainly, of important human and civil rights, but forgetting or underestimating the strategic objectives of the political struggle in favor of the great majorities. Finally, a proposal is made towards “pluriversity” and for the creation of a single and integrated Costa Rican university system.